LONELINES, INTERPERSONAL TRUST AND AFFILIATION NEEDS IN EARLY ADULTH USERS OF THE BUMBLE APP - Rafifah, Jihan; Effy Wardati Maryam (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to examine the relationship between loneliness, interpersonal trust, and the need for affiliation among early adults using the Bumble dating application. Method: Employing a quantitative correlational design, data were collected from users through standardized psychological scales measuring loneliness, interpersonal trust, and affiliation needs. Results: The analysis revealed a significant positive relationship between loneliness and affiliation needs, suggesting that individuals experiencing higher levels of loneliness are more driven to establish social connections. Interpersonal trust was also found to be positively related to affiliation needs, although the strength of this relationship was weaker compared to loneliness. Novelty: This study offers a contemporary perspective by contextualizing the psychological dynamics of loneliness and trust within the digital environment of online dating, specifically the Bumble app. The findings contribute to the growing body of literature on digital-era social behavior and highlight the need for targeted interventions to enhance psychological well-being through the facilitation of meaningful online social interactions.